How do you solve #5x^2 + 7x = 6 # using the quadratic formula?

1 Answer
Apr 1, 2017

Answer:

Using the quadratic formula, #x =# #(-b+- sqrt(b^2-4ac))/(2a)#, we get that #x =-2, 0.6#

Explanation:

Rearrange the equation so that it becomes: #5x^2+7x-6=0#

The quadratic formula is: #x =# #(-b+- sqrt(b^2-4ac))/(2a)#

In our equation above,
#a=5#
#b=7#
#c=-6#

Plugging these values into the quadratic equation gives:

#x =# #(-7+- sqrt(7^2-4(5)(-6)))/(2(5))#

#x =# #(-7+- sqrt(49+120))/(10)#

#x =# #(-7+- sqrt(169))/(10)#

#x =# #(-7+- 13)/(10)#

#x =-2, 0.6#